2016
DOI: 10.1016/j.jcbs.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Better living with illness: A transdiagnostic acceptance and commitment therapy group intervention for chronic physical illness

Abstract: Background: Long term conditions are on the rise and are associated with increased risk of psychological problems. Commonalities across long term conditions suggests a transdiagnostic psychological intervention may be beneficial. An Acceptance and Commitment Therapy (ACT) group intervention was evaluated for people with long term physical health conditions. Methods: Participants with long term physical health conditions were invited to an ACT group (n=53). Measures were completed at assessment, pre, post and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 58 publications
3
39
0
1
Order By: Relevance
“…Moreover, the results of this study show the durability of the ACT method in increasing the psychological flexibility of the patients with thalassemia in the follow-up phase. This finding agrees with the studies that have reported the efficacy of ACT in improving psychological problems of different disorders even after one or two years (Brassington et al, 2016;Lappalainen et al, 2014;McCracken & Gutiérrez-Martínez, 2011;Sianturi et al, 2018). It can be said that patients learn to take an active stand in the world and make their lives based on ACT strategies (Flaxman et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the results of this study show the durability of the ACT method in increasing the psychological flexibility of the patients with thalassemia in the follow-up phase. This finding agrees with the studies that have reported the efficacy of ACT in improving psychological problems of different disorders even after one or two years (Brassington et al, 2016;Lappalainen et al, 2014;McCracken & Gutiérrez-Martínez, 2011;Sianturi et al, 2018). It can be said that patients learn to take an active stand in the world and make their lives based on ACT strategies (Flaxman et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Besides, there are more examples of the studies on ACT use as an effective method to deal with psychological complications of a variety of diseases for instance anxiety in patients with stroke (Sianturi, Keliat, & Wardani, 2018) or other chronic physical illnesses (Brassington et al, 2016). However, to the best of our knowledge, no research has ever tried to evaluate the efficacy of ACT method to improve psychological problems in patients with thalassemia.…”
mentioning
confidence: 99%
“…Group discussions, experiential exercises and mindfulness practice (see Table 1 ) will be led by a psychologist who has been trained in ACT and is experienced in treating chronic pain. The content of the sessions will be adapted from an ACT treatment manual used in a recently published study [ 29 ] and available to members of the Association for Contextual Behavioral Science (ACBS) from the website http://www.contextualscience.org/better_living_with_illness . Written supplementary material will be provided each week and participants will be encouraged to spend time reviewing the material at home.…”
Section: Methodsmentioning
confidence: 99%
“…Brassington et al . () found that ACT can promote adjustment and improve quality of life for people struggling with physical symptoms. In addition to ‘broad‐spectrum’ CBT evidence, there is also some evidence for brief psychodynamic approaches.…”
Section: Introductionmentioning
confidence: 99%